A STUDY ON STUDENTS’ DIFFICULTIES IN LISTENING AT STUDENTS CLASS XI IN MA AL-MUNAWWARAH PAGUYAMAN - Nur Fitriyani Rahim (LP2M IAIN Sultan Amai Gorontalo, 2017)
The objective of this research was to find the cause of students’ difficulties in listening grade XI in MA Al-Munawwarah Paguyaman. This type of research was descriptive qualitative method by using qualitative approach (qualitative research). This research was conducted at MA Al-Munawwarah Paguyaman. The subject of research were the students of grade XI consist of 16 people. Data collection techniques used structured interviews and interviews guideline. Data analysis in this research used interactive model analysis. The result revealed that students have difficulty in listening to English text on linguistic factors and non-linguistic factors such as lack of motivation, material duration, and difficulty concentrating.